ผลของอัตราส่วนสารสีต่อสารยึดต่อการยึดติดและคุณภาพสิ่งพิมพ์ของหมึกเฟล็กโซกราฟีฐานน้ำบนพอลิโอลิฟิน - จิตราพร ศรีทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This research aim was to study the effects of phthalocyanine blue pigment-to-modified polyurethane binder ratio in the water-based flexographic inks on adhesion and printing qualities of olefin films. Olefin films were treated with corona discharge. The contact angles on non-treated and treated films were measured and their energy surfaces were calculated. The pigment-to-binder-to-water ratio for pigment dispersion was observed by Daniel flow point method. Pigment dispersion by ball mill with an optimal ratio of pigment: binder: water: dispersant was investigated. The pigment particle sizes from dispersion at various grinding times were measured. The twelve ink formulations were prepared with pigment dispersion paste, fixed thickener content and various contents of binder, carnuba wax and surfactant. The surface tension, pH and viscosity of the prepared inks were measured. Each ink formulation was printed on LLDPE and CPP films with IGT-F1. The mottle, adhesion, gloss, color value, density and rub resistant of the prints were investigated. It was found that the surface energy and roughness of LLDPE and CPP films increased with corona discharge. However, some part of CPP film surface was damaged. When binder content increased, the particle size of pigment was less at the same dispersion time. Non-ionic, modified fatty acid derivative dispersant gave better reduction the particle size and no flocculation of pigment in inks. When binder content in pigment-to-binder ratio increased, viscosity of ink decreased. Pigment-to-binder ratio affected gloss. The color difference and density decreased with increasing binder content. Carnuba wax content affect mottle and gloss. The carnuba wax increased rub resistant on CPP film, but it decreased rub resistant on LLDPE film. When surfactant increased, the surface tension and viscosity of ink was decreased. Surfactant decreased gloss but increased adhesion and rub resistance of CPP film. When used excess surfactant, prints mottle on LLDPE and CPP films increased. The prepared water-based flexographic ink could adhesion on polyolefin films and provided good printing qualities.